Antimicrobial properties of tamarindus indica linn leaf extracts - Ngulube, Leratiloe M. (Midlands State University, 2017)
Tamarindus indica l leaves extract was evaluated against six bacterial strains (2 Gram-positive and 4 Gram-negative) known to cause food spoilage. Functional groups of Tamarindus indica l leaves were evaluated using the Fourier transform infrared (FTIR) spectroscopy. The leaves were extracted by the Soxhlet extraction using aqueous and organic solvents (acetone, ethanol and methanol). Stock solution of the extracts was prepared by dissolving 0.8g of each extract in 2ml dimethyl sulphoxide (DMSO) to obtain a concentration of 400mg/ml and the concentration of 200mg/ml was prepared by serial doubling dilution of stock solution and 2ml of DMSO was added. Inoculum suspension was prepared by suspending appropriate colonies of the test microorganisms in sterile distilled water. The 0.5 McFarland of 1% barium chloride and 1% sulphuric acid was used to standardize the inoculum. The antimicrobial activity of the concentrated extracts was evaluated by determination of the zones of inhibition against the test microorganisms using the disc diffusion method. The results of the FTIR revealed the presence of primary and secondary amines and amides, carboxylic acid, alkenes and alkanes, fluorides, amines and aromatics. The extracts were active against both gram-positive and gram-negative bacteria. The activity of the plant extracts could have been affected by different temperature ranges, nature of the tree of freshness and dryness of the leaves. All extracts showed appreciable inhibition on the test microorganisms with the zones of inhibition ranging from 6.4 mm-19.8mm and ethanol extracts showed a broader spectrum of activity against the test microorganisms. Results obtained of this study indicate that Tamarindus indica l has broad spectrum antibacterial activity and a potential source of new classes of natural preservatives that could be useful for replacement of synthetic food grade preservatives